2010
DOI: 10.3382/ps.2010-00865
|View full text |Cite
|
Sign up to set email alerts
|

Performance and immune responses to dietary β-glucan in broiler chicks

Abstract: During the first week posthatch, the avian immune system is immature and inefficient at protecting chicks from invading pathogens. Among immunomodulators, beta-glucans are known as biological response modifiers due to their ability to activate the immune system. Current research suggests that beta-glucans may enhance avian immunity; however, very little is known about their influence on regulation of immune function. A study was performed to evaluate the effects of dietary beta-glucan on growth performance, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 25 publications
2
57
2
1
Order By: Relevance
“…β-glucan supplementation has been shown to alter the cytokine profiles of unchallenged, day-old chicks (Cox et al, 2010). Compared with unsupplemented controls, broiler chicks receiving β-glucan from Saccharomyces cerevisiae were shown to down-regulate IL-8.…”
Section: Glucansmentioning
confidence: 99%
See 4 more Smart Citations
“…β-glucan supplementation has been shown to alter the cytokine profiles of unchallenged, day-old chicks (Cox et al, 2010). Compared with unsupplemented controls, broiler chicks receiving β-glucan from Saccharomyces cerevisiae were shown to down-regulate IL-8.…”
Section: Glucansmentioning
confidence: 99%
“…This enzyme results in the production of nitric oxide which reacts with superoxide anions to generate toxic derivatives which allow the macrophage to kill several types of pathogens. Cox et al (2010) reported upregulation of iNOS in response to β-glucan supplementation, implying increased capacity of macrophages to destroy pathogens.…”
Section: Glucansmentioning
confidence: 99%
See 3 more Smart Citations